Hypoxia-alleviated nanoplatform to enhance chemosensitivity and sonodynamic effect in pancreatic cancer. (1st November 2021) - Chen, Jifan; Bao, Yuheng; Song, Yue; Zhang, Cong; Qiu, Fuqiang; Sun, Yu; Xin, Lei; Cao, Jing; Jiang, Yifan; Luo, Jiali; Zhang, Chao; Wang, Guowei; et al.
Abstract: Pancreatic cancer is a severe disease that threatens human health. The hypoxic tumor microenvironment in pancreatic cancer leads to resistance to conventional therapies and helps to maintain tumor malignancy. First-line drugs present the disadvantage of systemic side effects, and a synergistic method with sonodynamic therapy (SDT) has been established as an emerging approach. In this study, we produced hypoxia-alleviating nanoplatforms (denoted as PZGI NPs) with zeolitic imidazolate frameworks-90 (ZIF-90) nanoparticles nucleating on platinum (Pt) nanoparticles and co-loaded with gemcitabine and IR780. This platform can catalyze peroxide to oxygen with loaded Pt nanoparticles to alleviate tumor hypoxia. Moreover, the loaded drugs could be quickly released in the lysosome microenvironment, which has a low pH value and high ATP level microenvironment in the mitochondria. This strategy could enhance the sensitivity of cancer cells to chemotherapy. Further, under ultrasound exposure, it could transfer the produced oxygen into a highly cytotoxic singlet oxygen for the augmented sonodynamic effect. Therefore, this multifunctional hypoxia-alleviating nanoplatform offers a promising strategy for chemo-sonodynamic therapy against pancreatic cancer. Highlights: ZIF-90-derived nanoplatforms lowered hypoxia in the tumor microenvironment. Pt nanoparticles were used as nanozymes to catalyze endogenous H2 O2 into oxygen. The alleviation of hypoxia was beneficial to the increase in chemosensitivity. The alleviation of tumor hypoxia increased the efficacy of Sonodynamic therapy.